Feedforward backpropagation, genetic algorithm approaches for predicting reference evapotranspiration - Abdullah S.S.; Malek M.A.; Abdullah N.S.; Mustapha A. (Penerbit Universiti Kebangsaan Malaysia, 2023)
artificial neural network; back propagation; evapotranspiration; genetic algorithm; resource scarcity; semiarid region; water demand; Baghdad [Iraq]; Iraq